Interleukin-18 levels in adult dengue fever and dengue hemorrhagic fever (Medical Journal of Indonesia, 2004)
Interleukin (IL)-18 ( interferon-Î³ inducing factor) is one of cytokines, produced by macrophage, take part in differentiation T-helper (Th) to Th1 and interferon Î³Â producing. T helper1 play role in cellular immunity especially in viral infection include dengue. A descriptive correlative study has done to know the correlation between IL-18 levels and disease severity in admitted dengue fever (DF) and dengue hemorrhagic fever (DHF) patients. In 42 subjects consist of 20 (47.6%) DF and 22 (53.3%) DHF (grade I to IV WHO criteria, 1999) showed that IL-18 levels significantly higher in DHF than DF patients. There are significant correlation between IL-18 levels and hematocrit and low platelet value. This study supports the possible role of IL-18 in pathogenesis DHF in adults. (Med J Indones 2004; 13: 86-9)Keywords: dengue, dengue hemorrhagic fever, IL-18, cytokine, pathogenesis